2019
DOI: 10.1002/open.201900263
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Kraft Lignin with Dodecyl Glycidyl Ether

Abstract: Kraft lignin (KL) is extensively produced in industry but is mainly burned as fuel. To broaden its use, KL was grafted with dodecyl glycidyl ether to alter its thermal properties. The reaction of KL with dodecyl glycidyl ether (DGE) was analyzed using nuclear magnetic resonance (NMR), Fourier infrared spectroscopy (FT‐IR) and elemental analysis. Alternatively, KL was methylated to mask its phenolic hydroxy groups to investigate how phenolic hydroxy groups impact the grafting of the alkyl chain of DGE onto lign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Compared with the values of M w of PEG200L-140 ( M w : 4130) and MPEG-n4L-140 ( M w : 3150), the lower M w of CGL-140 ( M w : 2560) supported the result of the lower T g and T f values. The T g value of lignin derivatives depends on their molecular weight, cross-linking structure, and hydrogen bonds . Several studies have demonstrated the enhancement of thermal properties by chemically modifying kraft lignin with alkyl chains. , The esterification of the hydroxy group in lignin via the addition of long aliphatic chains reduced T g because the ester substituent decreased the number of hydrogen bonds in the lignin molecule, increasing the free volume in the molecule and consequently enhancing the mobility of the chains .…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the values of M w of PEG200L-140 ( M w : 4130) and MPEG-n4L-140 ( M w : 3150), the lower M w of CGL-140 ( M w : 2560) supported the result of the lower T g and T f values. The T g value of lignin derivatives depends on their molecular weight, cross-linking structure, and hydrogen bonds . Several studies have demonstrated the enhancement of thermal properties by chemically modifying kraft lignin with alkyl chains. , The esterification of the hydroxy group in lignin via the addition of long aliphatic chains reduced T g because the ester substituent decreased the number of hydrogen bonds in the lignin molecule, increasing the free volume in the molecule and consequently enhancing the mobility of the chains .…”
Section: Resultsmentioning
confidence: 99%
“…Methylation occurred both in phenolic and enolic hydroxyl groups, rendering lignin insoluble in bisulfite. Today, methylation in dimethyl sulfoxide (DMSO) is one of the most common strategies to modify lignin, making the derivatives less reactive and less thermally stable than the original hydroxylated lignin (Alwadani and Fatehi 2019;Shen et al 2020;Wang et al 2015). Furthermore, methylated lignins are more compatible with polymeric materials such as polyethers, polyesters, polyethylene, and natural rubber (Wang et al 2015) (Table 2).…”
Section: Methylationmentioning
confidence: 99%
“…By masking the reactive phenols within lignins, improved thermal stability, reduced hygroscopicity, and lower glass-transition temperature can be achieved. 2,3,7–10 Furthermore, the yields of aromatic compounds obtained by depolymerization of lignins can also be significantly improved by methylation of the phenols. 11,12 However, classical methylation agents such as dimethyl sulfate and iodomethane are toxic, expensive, and lead to processes characterized by poor atom economy.…”
Section: Introductionmentioning
confidence: 99%